Thermodynamically stable MOF showing a highly rare four-connected hxg-d-4-Cccm net with self-penetration, polyrotaxane, and polycatenane multi-features. Issue 10 (26th January 2016) - Zhang, Le; Feng, Xue Feng; Meng, Pan Pan; Gong, Le Le; Luo, Feng
Abstract : Herein, we report the first case of MOFs showing the coexistence of self-penetration, polyrotaxane, and polycatenane multi-features. Abstract : Two different crystals, namely Zn2 (L)2 (AzDC)2 ·(H2 O)2 (1 ) and Zn2 (L)2 (AzDC)2 (2 ) (L = N 2, N 6 -di(pyridin-4-yl)pyridine-2, 6-dicarboxamide, H2 AzDC = azobenzene-4, 4′-dicarboxylic acid), have been co-crystallized in a one-pot reaction, where1 is a thermodynamically stable product, as only a few crystals of2 are observed in this system and after holding in the original solution for more than three hours the crystals of2 transform to become1 . Notably, 1 represents a highly rare hxg-d-4-Cccm net with self-penetration and polyrotaxane and polycatenane multi-motifs, whereas a common sql net with three-fold interpenetration is observed for2 .